The Factors Affecting STIE Yapis Dompu Students’ Interest in Entrepreneurship - Ega Saiful Subhan; Budi Eko Soetjipto; Cipto Wardoyo (Journal of Social Science, 2022)
This research aims to acknowledge the effect of non-formal education, social and family environment, information technology, and business capital on entrepreneurial interest in STIE Yapis Dompu students. This research is a quantitative descriptive and analytic study with a survey method at STIE Yapis Dompu titled "Factors Affecting Entrepreneurial Interests in STIE Yapis Dompu Students. "The analytical technique used to measure the factors that influence entrepreneurial interest in STIE Yapis Dompu students is multiple linear regression using the SPSS version 21 program for windows. The results show that: 1) Partially, there is a significant effect of social and family environment variables and business capital on the entrepreneurial interest of STIE Yapis Dompu students. Meanwhile, the variables of non-formal education and information technology have no significant effect on the entrepreneurship interest of STIE Yapis Dompu students. 2) Simultaneously, the variables of non-formal education, social and family environment, information technology, and venture capital significantly affect the entrepreneurship interest of STIE Yapis Dompu students. The results of this study produce a coefficient of determination (R2) of 0.485, which means the ability of the four independent variables to explain the variable interest in entrepreneurship is 48.5%, while the rest (100% - 48.5% = 51.5%) is explained by the following factors: other factors outside the study. 3) The most dominant variables from other variables are the social and family environment. The assumption that non-formal education has a dominant influence on the entrepreneurial interest of STIE Yapis Dompu students has not been proven true.